Computing cyclic invariants for molecular graphs1. Issue 2 (25th July 2017) - Berger, Franziska; Gritzmann, Peter; de Vries, Sven
Abstract : Ring structures in molecules belong to the most important substructures for many applications in Computational Chemistry. One typical task is to find an implicit description of the ring structure of a molecule. We present efficient algorithms for cyclic graph invariants that may serve as molecular descriptors to accelerate database searches. Another task is to construct a well‐defined set of rings of a molecular graph explicitly. We give a new algorithm for computing the set of relevant cycles of a graph. © 2017 Wiley Periodicals, Inc. NETWORKS, Vol. 70(2), 116–131 2017